STRUCTURE-FORMATION IN ROLLED WIRE OF ALLOY STEEL OF WELDING PURPOSE AT ISOTHERMAL EQUALIZING - A. V. Sychkov; M. A. Zhigarev; A. V. Peregudov; S. Ju. Zhukova; T. M. Filippova (Литьë и металлургия, 2011)
Two series of experiments on investigation of structure formation in rolled wire of alloy steel of welding function are carried out.